2013
DOI: 10.1001/jama.2013.8399
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Type 1 Diabetes in Finland

Abstract: The incidence of type 1 diabetes (T1D), one of the most prevalent chronic disease in children, has increased worldwide. 1 The highest recorded incidence in children younger than 15 years was 64.2 per 100 000 person-years in Finland in 2005. 2 We examined the incidence rates between 2006 and 2011 in Finnish children younger than 15 years as well as the 32-year trend (1980-2011). Methods | All children with newly diagnosed T1D were ascertained using several nationwide registers as previously described. 2 Age-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
195
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(211 citation statements)
references
References 4 publications
12
195
2
2
Order By: Relevance
“…Previously, stabilization of rates was observed from 2003 to 2006. Similar results were obtained in some high risk countries, which reached a plateau in the disease incidence and shift toward younger age at disease onset 19,20 . According to some authors, the increase of T1DM incidence is the consequence of earlier clinical presentation rather than of global increase of incidence, earlier exposure to external factors for the development of T1DM, and faster progression of the subclinical disease process to overt diabetes 21 .…”
Section: Discussionsupporting
confidence: 87%
“…Previously, stabilization of rates was observed from 2003 to 2006. Similar results were obtained in some high risk countries, which reached a plateau in the disease incidence and shift toward younger age at disease onset 19,20 . According to some authors, the increase of T1DM incidence is the consequence of earlier clinical presentation rather than of global increase of incidence, earlier exposure to external factors for the development of T1DM, and faster progression of the subclinical disease process to overt diabetes 21 .…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of these agonists in the environment is variable, depending on the geographic location and has been changing over time. The exposure of human beings to nicotine, for example, has been changing over the past decades due to decreased prevalence of active and passive smoking in most countries (36,37). Choline on the other hand, is contained in many types of foods, particularly in eggs, liver, and heart (38).…”
Section: Discussionmentioning
confidence: 99%
“…A study from the US Virgin Islands reported an 'epidemic-like' spike in incidence in 2006, when the incidence increased threefold compared with the previous year [8]. In Finland, a steeper rise in incidence in the early 1990s contributed a significant non-linear component to the incidence rate trend, resulting in a curvilinear, rather than cyclical, temporal trend between 1980 and 2005 [2]. Other studies have observed a non-linear temporal trend of levelling off, or plateauing, in the incidence of childhood type 1 diabetes mellitus in recent years [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…However, the rates of increase and temporal trends are variable [1], Electronic supplementary material The online version of this article (doi:10.1007/s00125-015-3709-2) contains peer-reviewed but unedited supplementary material, which is available to authorised users. and a possible plateauing of incidence has been reported in Sweden, Finland [2] and Norway [3], as well as in Australia [4].…”
Section: Introductionmentioning
confidence: 99%